2013
DOI: 10.1007/s10290-013-0155-4
|View full text |Cite
|
Sign up to set email alerts
|

Does foreign aid promote recipient exports to donor countries?

Abstract: Registro de acceso restringido Este recurso no está disponible en acceso abierto por política de la editorial. No obstante, se puede acceder al texto completo desde la Universitat Jaume I o si el usuario cuenta con suscripción. Registre d'accés restringit Aquest recurs no està disponible en accés obert per política de l'editorial. No obstant això, es pot accedir al text complet des de la Universitat Jaume I o si l'usuari compta amb subscripció. Restricted access item This item isn't open access because of publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 48 publications
5
46
1
1
Order By: Relevance
“…This supported their interpretation that market knowledge through interpersonal relations is an important driver of exports. However, these results were obtained without controlling for unobservable heterogeneity related to each bilateral relationship, and so this could bias the estimates, as pointed out in Nowak- Lehmann et al (2013). Finally, Martínez-Zarzoso et al (2015a), also in a multi-country setting, found that, in general, donors' bilateral aid has positively affected their exports to developing countries.…”
Section: Literature Reviewmentioning
confidence: 95%
“…This supported their interpretation that market knowledge through interpersonal relations is an important driver of exports. However, these results were obtained without controlling for unobservable heterogeneity related to each bilateral relationship, and so this could bias the estimates, as pointed out in Nowak- Lehmann et al (2013). Finally, Martínez-Zarzoso et al (2015a), also in a multi-country setting, found that, in general, donors' bilateral aid has positively affected their exports to developing countries.…”
Section: Literature Reviewmentioning
confidence: 95%
“…The authors analyze the effects from various foreign development assistance variables on both recipient and donor country exports and find a particularly strong relation between aid in the form of technical assistance and exports in both directions, supporting their interpretation that market knowledge through interpersonal relations is an important driver for exports. However, given that unobservable heterogeneity related to each bilateral relationship was not controlled for, this may bias the estimates, as pointed out by Nowak-Lehmann et al (2013).…”
Section: Empirical Literature On Aid and Tradementioning
confidence: 99%
“…The empirical studies of Nowak-Lehmann et al (2013) and Martí nez-Zarzoso et al (2014) reveal that the US exports to developing countries are positively associated with its bilateral aid. However, the exports of recipient countries are not promoted by the aid (Nowak-Lehmann et al, 2013).…”
Section: Us Foreign Aidmentioning
confidence: 99%
“…To assure that the change in recipients' trade can be traced back to the change in foreign aid, Nowak- Lehmann et al (2013) attributed it to the role played by unobservable or unquantifiable characteristics that affect donor-recipient relations, such as reputation, mutual trust and support, goodwill and familiarity as well as customer relations, distribution channels and a better adaptation to the formal and informal market environment. However, they did not find significant effect of aid on exports of recipient countries in an empirical perspective.…”
Section: Impact Of Aid On Recipients' Trade Flowsmentioning
confidence: 99%